PENINGKATAN KETRAMPILAN POSYANTEK NATURI GAMPONG TEUBANG PHUIACEH BESAR, DALAM MEMBUAT SABUN CUCI PIRING EKONOMIS - Kiki Rishki Ananda; Ruskhanidar; Kumita (JURNAL KREASI RAKYAT, 2025)
The availability of lime or lemon in Aceh is sufficient, even exceeding household needs, so it can be processed into other innovations for domestic use, such as dishwashing soap. Lime contains various beneficial chemical compounds, including: citric acid, which functions as a chelating agent that helps break down dirt and grease; and limonene, a natural compound that acts as a degreasing agent while also providing a fresh aroma.The innovation of producing organic dishwashing soap is highly needed by the community. Economically, the benefits of this dishwashing soap can help reduce household expenses, allowing families to reallocate their budget to other needs, such as fulfilling nutritional requirements. Environmentally, this eco-friendly dishwashing soap can help preserve water quality by reducing household waste pollution. For lime and suji leaf farmers, this innovation can increase the sales of their agricultural products, thereby boosting cross-sectoral economic growth at the grassroots level.